2017
DOI: 10.1107/s2052520616016450
|View full text |Cite
|
Sign up to set email alerts
|

A new tecton with parallel halogen-bond donors: a path to supramolecular rectangles

Abstract: A new tecton, 1,8-diiodoethynylanthracene, with two halogen-bond donor sites was synthesized and characterized. This tecton is capable of forming two parallel halogen bonds at once, which makes it a useful building block for the construction of a variety of supramolecular squares and rectangles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…114 A similar design, using 1,8-bis(iodoethynyl)anthracene as a halogen bond donor template, was utilized by the Aakeroÿ group to steer molecules of trans-1,2-bis(4-pyridyl)ethylene into rectangleshaped tetramolecular assemblies. 115 Halogen bond-driven cocrystallization was used by Zhu and co-workers 116 to enable a green [2 + 2] photodimerization process involving vitamin K 3 as the reactant (Figure 16). Cocrystal formation involving vitamin K 3 with either 1,4diiodo-or 1,4-dibromotetrafluorobenzene leads to the formation of linear halogen-bonded chains whose stacking brings the carbon−carbon double bond (CC bond) in orientations suitable for [2 + 2] photodimerization.…”
mentioning
confidence: 99%
“…114 A similar design, using 1,8-bis(iodoethynyl)anthracene as a halogen bond donor template, was utilized by the Aakeroÿ group to steer molecules of trans-1,2-bis(4-pyridyl)ethylene into rectangleshaped tetramolecular assemblies. 115 Halogen bond-driven cocrystallization was used by Zhu and co-workers 116 to enable a green [2 + 2] photodimerization process involving vitamin K 3 as the reactant (Figure 16). Cocrystal formation involving vitamin K 3 with either 1,4diiodo-or 1,4-dibromotetrafluorobenzene leads to the formation of linear halogen-bonded chains whose stacking brings the carbon−carbon double bond (CC bond) in orientations suitable for [2 + 2] photodimerization.…”
mentioning
confidence: 99%
“…For instance, XB triangular motifs, formerly observed in the hexachlorobenzene and hexabromobenzene crystal structures where halogen atoms bear at the time anchoring electrophilic and nucleophilic sites leading to 180°/120° geometries, 27 were then engineered by directing self-complementary donor and acceptor sites at an angle of 60 o along the sides of an equilateral triangle using triiodoimidazolium 28 or iodoethynylpyridine 29 30 The targeted formation of discrete, but heteromolecular halogen-bonded assemblies is illustrated for example by rectangular motifs formed upon co-crystallization of complementary ditopic XB donors such as 1,8diiodoethynylanthracene and ditopic XB acceptors such as 1,2-bis(4pyridyl)ethane (bpe) (Scheme 1c). 31 The reverse situation is also reported, from a U-shaped anthracene-based ditopic Lewis base with linear ditopic halogen bond donors. 32 To the best of our knowledge, chalcogen-bonded, discrete, heteromolecular supramolecular architectures have not been reported so far and still remain challenging.…”
mentioning
confidence: 93%
“…37 We envisioned this alkynyl approach to be a potential route to design and engineer supramolecular heteromolecular macrocycles under ChB control. Inspired from the work on 1,8-diiodoethynylanthracene XB donor (Scheme 1c), 31 we considered replacing both iodine atoms with telluroalkyl moieties, anticipating that the strong activation of a sigma-hole on the tellurium atom in the prolongation of the (C≡C)−Te bond could similarly favor supramolecular assembly into discrete rectangles upon co-crystallization with a ditopic Lewis-base, as shown in Scheme 2.…”
mentioning
confidence: 99%
“…One way to overcome this problem is by using cocrystals. In this case, other molecules and intermolecular interactions will be competing to stabilize the crystal structure, allowing a better insight into their relative importance. , …”
Section: Introductionmentioning
confidence: 99%
“…In this case, other molecules and intermolecular interactions will be competing to stabilize the crystal structure, allowing a better insight into their relative importance. 4,5 While studying the intermolecular interactions of small molecules that have the possibility of presenting different intermolecular interactionshydrogen bonds (HBs), halogen bonds (XBs), and interactions between aromatic rings (π•••π and C−H •••π)we found that the structure of perfluorophenyl-4pyridinylmethanimine (1) presents an unanticipated NC− H•••F interaction. It was unexpected and exciting because, although there have been many studies of organic, coordination, and supramolecular chemistry of Schiff bases and their applications, there have been no systematic studies, as far as the authors know, of Schiff bases as HB donors−acceptors.…”
Section: ■ Introductionmentioning
confidence: 99%